Density dependence of transient electron thermal transport property in LHD. (29th October 2018) - Kobayashi, T.; Ida, K.; Ii Tsujimura, T.; Inagaki, S.; Tokuzawa, T.; Tsuchiya, H.; Tamura, N.; Igami, H.; Yoshimura, Y.; Itoh, S.-I.; Itoh, K.
Abstract: In this paper, we investigate data from the density scan experiment in order to clarify how the transport hysteresis width depends on the density. As the line averaged density increases, the hysteresis width almost monotonically decreases. To discuss the physical mechanism of the hysteresis formation, a theoretical model describing the direct response of the fluctuation amplitude to the heating is examined. The model predicts that decreasing density enhances the hysteresis width in the turbulent thermal transport, which is not in contradiction with the present observation. It is found that the model tends to estimate the parameter window in which the hysteresis emerges narrower than the experimental observation.